Correlates of loneliness in older persons living with HIV. Issue 7 (2nd July 2020) - Yoo-Jeong, Moka; Hepburn, Kenneth; Holstad, Marcia; Haardörfer, Regine; Waldrop-Valverde, Drenna
ABSTRACT: Loneliness poses a significant risk for morbidity and mortality in the context of older adulthood. Research shows that older persons living with HIV (PLWH) often face increased and complex vulnerability in terms of physical and psychosocial needs which may promote loneliness. The current study sought to identify correlates of loneliness in a sample of 146 older PLWH (age ≥50) recruited from an outpatient HIV clinic in Atlanta, GA. Participants completed a survey on loneliness, depression, HIV-related stigma, social network size, HIV-disclosure status, disease burden, and demographics. HIV biomarkers were abstracted from electronic medical records. Participants were predominantly male (60%) and African American (86%). Twelve percent ( n = 17) reported past homelessness/unstable housing. Multivariable modeling revealed that depression and HIV-related stigma explained 41% of the variance in loneliness, above and beyond the effects of past homelessness/unstable housing and disease burden ( R 2 = 0.41, F (7, 138) = 13.76, p < .001). Findings suggest that targeting HIV-related stigma and depression may reduce loneliness in older PLWH, but more studies are needed to elucidate causal pathways. A greater understanding of the mechanisms by which loneliness affects health among older PLWH could help better inform efforts to improve health in this patient population.